Implikasi Pendidikan dari Al-Quran Surat Adz-Dzariyat Ayat 56 tentang Tujuan Penciptaan Manusia terhadap Upaya Pendidikan dalam Membentuk Manusia yang Taat Beribadah - Intan Taufikurrohmah (Bandung Conference Series: Islamic Education, 2022)
Abstract. God created humans by being given advantages over other creatures, namely reason to carry out the purpose of life on earth as QS. Adz-Dzariyat verse 56 is to worship Allah SWT. because if people do not fulfill their obligations, they will feel or be considered empty-hearted and meaningless in their lives. In order to be able to carry out the obligations/goals of life, people must be educated so that they can become obedient people, basically the main purpose of education in Islam according to the Al-Quran is to build people who are aware of their basic duties while in the world so that in living life including carrying out the education process, both from students and educators, should be based on a form of devotion to Allah SWT alone. Education becomes a container for humans to form and develop the mind to carry out its obligations, in forming the mind is of course related to the intellectual, emotional, spiritual. therefore, in order to form people who obey Allah SWT, various educational efforts are needed to make it happen. The purpose of this research is to find out the opinions of commentators on QS Adz-Dzariyat verse 56, to understand the essence of QS Adz-Dzariyat verse 56, to know the opinions of experts on educational efforts in shaping people who obey worship, to know the implications of education from Al-Quran Surat Adz -Dzariyat verse 56 about the purpose of human creation against educational efforts in forming people who obey worship. The essence that can be taken from QS. Adz-Dzariyat verse 56 that is: God created Jinn and humans only to worship, Parents and teachers must be educators from an early age to realize the purpose of human creation, In order to realize the purpose of human creation, it is necessary to make several efforts to develop the mind in order to be obedient human beings worship. Abstrak. Allah menciptakan manusia dengan diberi kelebihan dari makhluk lain yaitu akal untuk menjalankan tujuan hidupnya di muka bumi sebagaimana QS. Adz-Dzariyat ayat 56 yaitu untuk beribadah kepada Allah SWT. karena jika manusia tidak melaksanakan kewajibannya ia akan merasa atau dianggap kosong hatinya dan tidak bermakna hidupnya. Agar dapat melaksanakan kewajiban/ tujuan hidup, manusia harus dididik supaya bisa menjadi manusia yang taat beribadah, pada dasarnya tujuan pokok pendidikan dalam islam menurut Al-Quran adalah agar membangun insan yang sadar akan tugas pokok selama di dunia sehingga dalam menjalani kehidupan termasuk melaksanakan proses pendidikan, baik dari siswa maupun pendidik, harus didasari sebagai bentuk pengabdian kepada Allah SWT semata. Pendidikan menjadi sebuah wadah bagi manusia untuk membentuk serta mengembangkan akal untuk menjalankan kewajibannya, dalam membentuk akal tentunya berkaitan dengan intelektual, emosi, ruhani. maka dari itu untuk membentuk manusia taat beribadah kepada Allah SWT diperlukan berbagai upaya pendidikan untuk mewujudkannya. Tujuan dari penelitian ini yaitu Mengetahui pendapat para mufasir terhadap Q.S Adz-Dzariyat ayat 56, Memahami esensi dari Q.S Adz-Dzariyat ayat 56, Mengetahui pendapat para ahli mengenai upaya pendidikan dalam membentuk manusia yang taat beribadah, Mengetahui implikasi pendidikan dari Al-Quran Surat Adz-Dzariyat ayat 56 tentang tujuan penciptaan manusia terhadap upaya pendidikan dalam membentuk manusia yang taat beribadah. Esensi yang dapat di ambil dari QS. Adz-Dzariyat ayat 56 yaitu: Allah menciptakan Jin dan manusia hanya untuk beribadah, Orang tua maupun guru tentulah menjadi pendidik sejak dini untuk mewujudkan tujuan penciptaan manusia, Untuk mewujudkan tujuan penciptaan manusia tersebut perlu mengadakan beberapa upaya untuk mengembangkan akal agar dapat menjadi manusia yang taat beribadah.